Who’s Afraid of the Minimum Wage? Measuring the Impacts on Independent Businesses Using Matched U.S. Tax Returns - Nirupama L Rao; Max Risch (The Quarterly Journal of Economics, 2026)
Abstract A common concern surrounding minimum wage policies is their impact on independent businesses, which are often feared to be less able to bear or pass on cost increases. We examine how these typically small and medium-size firms accommodate minimum wage increases along product and labor market margins using a matched owner-firm-worker panel data set drawn from the universe of U.S. tax records over a 10-year period, and using state minimum wage changes as identifying variation. We find that on average, firms in highly exposed industries do not substantially reduce employment—they do not lay off workers but moderately reduce part-time hiring. Instead, these firms are able to fully finance the new labor costs with new revenues, leaving average owner profits unchanged. Higher wage floors, however, forestall entry, particularly for less productive firms, reducing the number of independent firms operating in these industries by roughly 2%. Yet these industries do not shrink; instead, incumbent responses and strong positive selection among entrants reshape industries that rely heavily on low-wage workers, yielding fewer but more productive firms after the cost shock. We also take a worker-level perspective to examine how potentially vulnerable individuals are affected by minimum wage increases. Using panels of low-earning and young workers, we find that their average earnings rise substantially with the minimum wage, while they are no less likely to be employed. Worker transitions indicate that minimum wage increases boost retention and that worker reallocation from independent firms toward corporations buffers disemployment impacts from reduced hiring at independent firms.